2013
DOI: 10.2151/jmsj.2013-608
|View full text |Cite
|
Sign up to set email alerts
|

ENSO Regime Change since the Late 1970s as Manifested by Two Types of ENSO

Abstract: During the late 1970s, the El Niño-Southern Oscillation (ENSO) experienced a notable regime change, manifested by a change in amplitude, dominant ENSO period, and sea surface temperature anomaly (SSTA) propagation characteristics. The present study shows that these features of the ENSO regime change are associated with property changes of the canonical ENSO, i.e., cold-tongue (CT) type ENSO. Another signature of the ENSO regime change is manifested in the frequent occurrence of a warm-pool (WP) type ENSO that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…It is well known that the Bjerknes feedback (BF) makes a dominant contribution to ENSO evolution (e.g., Bjerknes, ; Capotondi, ; Fedorov & Philander, ; Jin, ; Karnauskas, 2013). Recently, Ren and Jin () emphasized that the BF also plays a dominant role in contributing to the growth of CP‐El Niño. Since the CTM can well represent the long‐term trend of the tropical Pacific under global warming (Li et al, ; Zhang et al, ), the BF of ENSO is expected to be modified by the CTM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the Bjerknes feedback (BF) makes a dominant contribution to ENSO evolution (e.g., Bjerknes, ; Capotondi, ; Fedorov & Philander, ; Jin, ; Karnauskas, 2013). Recently, Ren and Jin () emphasized that the BF also plays a dominant role in contributing to the growth of CP‐El Niño. Since the CTM can well represent the long‐term trend of the tropical Pacific under global warming (Li et al, ; Zhang et al, ), the BF of ENSO is expected to be modified by the CTM.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in terms of the differences in the location of the SST anomalies (SSTA) center over the tropical Pacific, the El Niño events could be distinguished two types, namely, the Eastern Pacific El Niño (EP‐El Niño) and Central Pacific El Niño (CP‐El Niño). Particularly, the CP‐El Niño also referred to the dateline El Niño, El Niño Modoki, or warm pool El Niño, has occurred frequently since 1980s (e.g., Ashok et al, ; Kao & Yu, ; Karnauskas, ; Kug et al, ; Larkin & Harrison, ; Ren & Jin, ; Ren et al, ; Takahashi et al, ; Yeh et al, ). The CP‐El Niño is characterized by maximum SSTA in the central equatorial Pacific, while the maximum SSTA in an EP‐El Niño (also referred to as the conventional El Niño) is located in the eastern equatorial Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this ambiguity, we exclude this specific event from our following analysis. We identify three EP El Niño events (1982/83, 1991/92, 1997/98) and five CP El Niño events (1994/95, 2002/03, 2004/05, 2006/07, 2009/10) based on the normalized Niño-3 (SST anomaly averaged over the region 58S-58N, 908-1508W) and Niño-4 (SST anomaly averaged over the region 58S-58N, 1608E-1508W) indices that have usually been used to define the two different types of El Niño (e.g., Kim et al 2009;McPhaden et al 2011;Ren and Jin 2011). The El Niño events with Niño-3 warming greater than Niño-4 warming during the winter season are defined as EP El Niño, and those with Niño-3 warming less than Niño-4 warming during the winter season are considered as CP El Niño (Fig.…”
Section: B Definition Of Enso Eventsmentioning
confidence: 99%
“…Correspondingly, the term ''eastern Pacific (EP) El Niño'' is used to identify the traditional El Niño events. In contrast, it seems that no clear change in the zonal location of SST anomalies is detected for La Niña events (e.g., Kug et al 2009;Kug and Ham 2011;Ren and Jin 2011), although this was challenged by some studies in terms of regional climate impacts (e.g., Cai and Cowan 2009;Zhang et al 2015). In this study, all La Niña events are classified into one category, since almost all events show a similar evolution in the meridional movement of central Pacific wind anomalies.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have suggested that the strengthening trade winds may be explained by the natural internal variability in the Pacific, such as the El Niño Modoki (EM; e.g., Sohn et al, ), the Interdecadal Pacific Oscillation (IPO; e.g., Dong & Zhou, , England et al, , Ma & Zhou, ), and the centennial‐scale variability (e.g., Giese & Ray, ; Ray & Giese, ). The EM (Ashok et al, ), also referred to the dateline El Niño (Larkin & Harrison, ), Central Pacific El Niño (Kao & Yu, ), or warm pool El Niño (Kug et al, ), has become increasingly common in the past three decades (e.g., Ashok et al, ; Ding et al, ; Ding et al, ; Feng & Li, ; Feng & Li, ; Kao & Yu, ; Karnauskas, ; Kug et al, ; Ren et al, ; Ren & Jin, ; Takahashi et al, ; Zhang et al, ; Zhang et al, , ). The EM is characterized by maximum sea surface temperature anomaly (SSTA) in the central equatorial Pacific, while the maximum SSTA in a conventional El Niño is located in the eastern equatorial Pacific.…”
Section: Introductionmentioning
confidence: 99%